2010
DOI: 10.1016/j.molcel.2010.06.021
|View full text |Cite
|
Sign up to set email alerts
|

PoxA, YjeK, and Elongation Factor P Coordinately Modulate Virulence and Drug Resistance in Salmonella enterica

Abstract: SUMMARY We report an interaction between poxA, encoding a paralog of lysyl tRNA-synthetase, and the closely linked yjeK gene, encoding a putative 2,3-β-lysine aminomutase, that is critical for virulence and stress resistance in Salmonella enterica. Salmonella poxA and yjeK mutants share extensive phenotypic pleiotropy including attenuated virulence in mice, an increased ability to respire under nutrient limiting conditions, hypersusceptibility to a variety of diverse growth inhibitors and altered expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
218
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(230 citation statements)
references
References 82 publications
11
218
0
1
Order By: Relevance
“…In all cases, we were able to show that EF-P was able to efficiently relieve the translation stalling. Consistent with our findings was the identification of proteins containing PPP, PPG, or APP as being down-regulated when the genes encoding EF-P, YjeA, or YjeK were deleted in Salmonella (8,13). However, we did not observe any significant stalling in the absence of EF-P at non-diprolyl containing motifs, such as RME, YIR, PFF, YIRYIR, nor at the GSCGPG motif found in PoxB (Figs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In all cases, we were able to show that EF-P was able to efficiently relieve the translation stalling. Consistent with our findings was the identification of proteins containing PPP, PPG, or APP as being down-regulated when the genes encoding EF-P, YjeA, or YjeK were deleted in Salmonella (8,13). However, we did not observe any significant stalling in the absence of EF-P at non-diprolyl containing motifs, such as RME, YIR, PFF, YIRYIR, nor at the GSCGPG motif found in PoxB (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…In bacteria, the translational arrest is relieved by the translation elongation factor P (EF-P), which binds to the stalled ribosomes and stimulates peptide bond formation (5,6). In Escherichia coli, EF-P is posttranslationally modified by YjeA, YjeK, and YfcM (EpmA, EpmB, and EpmC) (8)(9)(10) and the resulting lysinylation modification has been shown to be critical for the rescue activity of EF-P in vivo and in vitro (5,6). EF-P homologs exist in all archaea and eukaryotes, termed aIF-5A and eIF-5A, respectively (11).…”
mentioning
confidence: 99%
“…However, two recent studies also indicated that EF-P could act during elongation by facilitating the synthesis of proteins containing stretches of consecutive proline residues (5,6). EF-P is similar in size and shape to a tRNA and can be post-translationally modified by a lysyl-tRNA synthetase paralog, PoxA (7,8). In a reaction analogous to tRNA aminoacylation, PoxA activates (R)-␤-lysine and subsequently transfers it to a conserved residue (Lys-34) in EF-P (9).…”
mentioning
confidence: 99%
“…In a reaction analogous to tRNA aminoacylation, PoxA activates (R)-␤-lysine and subsequently transfers it to a conserved residue (Lys-34) in EF-P (9). Attachment of a ␤-lysyl moiety is necessary for EF-P functionality both in vivo and in vitro (2,8). Recent mass spectroscopy analyses identified a second posttranslational modification of EF-P involving hydroxylation of the C4(␥) or C5(␦) of ␤-lysyl-Lys-34 by YfcM (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation